Evaluation of non-penetrative captive bolt stunning as a method of slaughter for white sturgeon (Acipenser transmontanus) - Gross, Jackson A.; Bowman, Jennifer R.; Imai, Denise M.; Wong, Talia S.; Duarte, Toni L.; Boles, Sara E.; McGorrin, Robert J.; Yang, Xiang (Frontiers in Animal Science, 2024)
Abstract: Percussive stunning is a widely used and ethically supported method of stunning fish per welfare standards as part of a one- or two-step slaughter process. In this study, the use of a non-penetrative captive bolt (NPCB) gun was evaluated as an effective one-step method of improving welfare for juvenile and adult farmed white sturgeon (Acipenser transmontanus) at slaughter. A Jarvis HPS-1 NPCB was operated at pressures of 120, 135, and 145 PSI (827.37, 930.79, and 999.74 kPa, respectively) for juvenile sturgeon (n = 3 sturgeon per operating pressure) and 175, 200, and 225 PSI (1206.58, 1378.95, and 1551.32 kPa, respectively) for adult sturgeon (n = 3 sturgeon per operating pressure). Following a single strike, fish were assessed for jaw relaxation and a somatic response before being exsanguinated and transferred to an ice slurry. An hour after slaughter, fish heads were collected, and a section of cartilage containing the brain was removed and fixed in formalin for histological analysis of brain death. To evaluate fish recovery, juveniles (n = 100) and adult female sturgeon (n = 65) were monitored for two hours after a single exposure to 145 and 225 PSI, respectively. Histology results showed there was an effect between operating pressure and intracranial hemorrhage in juvenile sturgeon (p = 0.024). There was a greater meningeal-to-cerebral hemorrhage at 135 PSI compared to the 120 PSI group (p = 0.020) and a trend towards increased tissue damage from 120 PSI to 145 PSI (p = 0.056). Adults showed no significant difference in meningeal hemorrhage at any operating pressure. When investigating recovery rates, NPCB successfully stunned 100% of juvenile sturgeon at 145 PSI, and 225 PSI stunned 90% of adult sturgeon without recovery. These results demonstrate that the use of an NPCB gun is an improvement in animal welfare compared to repeated strikes, but a single application did not produce histological brain death; further research should be conducted to determine optimal pressures that result in immediate brain death.